RSA performance evaluation for privacy preserving scheme in internet of things [electronic resource] - Bahareh Maleki Alavi, 1981- (2013)
Thesis (Sarjana Sains Komputer (Keselamatan Maklumat)) - Universiti Teknologi Malaysia, 2013